Learning Environment: A Key for Academic Success in Business Administration Students at a Higher Education Institution - Ribadeneira-Pazmiño, Daniela; Noboa-Torres, María Lorena; Vásconez-Torres, Manolo Javier; Tamayo-Arellano, Vicente Rodrigo (International Journal of Interactive Mobile Technologies (iJIM), 2025)
A study was carried out with the purpose of analyzing the current scientific literature in Latin America and the Caribbean regarding academic performance, highlighting the scarcity of research related to the correlation between the perception of the learning environment and academic performance. The objective of the study was to examine the relationship between the learning environment and academic performance of fourth and fifth semester students of Business Administration in online blended mode in a higher education institution. The instrument used to evaluate the learning environment was the classroom environment scale (CES) in one hundred students, where the classroom learning environment was evaluated in four main categories: academic, institutional, safety and community. For academic performance, data such as end-of-semester grade point average (GPA), age and gender were collected. The results of the study revealed that there is an association between a positive classroom environment and better academic performance. In conclusion, the study determined that a positive and welcoming learning environment is related to better academic performance, while a negative learning environment is associated with lower grades.